Peculiarities of Choral Activity in General Education Schools: Analysis of Educators Approach - Kardasiene, Ausra (Jaunųjų mokslininkų darbai, 2018)
The article presents peculiarities of choral activity in general education schools. The evaluation of choral performance is presented in reference to the data of an empirical study with 92 music teacher participants. The research carried out showed that the artistic-musical culture of choirs and concert activity depends on many factors: the choir’s manager, the repertoire, the quantitative and qualitative composition of singers and the mastery of choir vocal technique. The insufficient number of hours allocated for additional education, sometimes unfavourable working conditions, very little support from school heads of choral artistic-musical culture are the biggest obstacles.
Keywords: choirs of general education schools; Šiauliai town choirs; peculiarities of choral singing at school